Management of organ motion in scanned ion beam therapy - Bert, Christoph; Herfarth, Klaus (Radiation oncology, 2017)
Scanned ion beam therapy has special demands for treatment of intra-fractionally moving tumors such as lesions in lung or liver. Interplay effects between beam and organ motion can in those settings lead to under-dosage of the target volume. Dedicated treatment techniques such as gating or abdominal compression are required. In addition 4D treatment planning should be used to determine strategies for patient specific treatment planning such as an increased beam focus or the use of internal target volumes incorporating range changes.
Gesehen am 30.05.2018